PERBANDINGAN KEKUATAN PENGELASAN LISTRIK DENGAN PENGELASAN GAS PADA MATERIAL BESI SIKU JIS G3101 - Dwi Atmaja Mukti; Rudy Poeng; Tertius V Y Ulaan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
The research was to compare two types of welding, i.e. electric welding and gas welding for the strength and the yield stress of a brackets made of angle steel conformÂ to JIS G 3101 material.TheÂ results of strength has been done by previous researcher (Tumurang, 2014), while this research doing the strength of gas welding. The research shows that electric welding gives a better effect than gas welding. The tensile stress is 33.865%better, and the yield stress is 48.843% better. It is concluded that the welding of the material JIS G 3101 brackets is more appropriate to use the electrical welding than using gases of welding. Keywords: Strength of welding, Angle steel, Tensile test.